Enhanced threat of tick-borne infections within cities? Assessing public health risks due to ticks in urban green spaces in Helsinki, Finland - Sormunen JJ; Kulha N; Klemola T; Mäkelä S; Vesilahti E-M; Vesterinen EJ (WILEY, 2022)
Most tick-related studies in Europe have been conducted in nonurban areas, but ticks and tick-borne pathogens also occur in urban green spaces. From a public health perspective, risks regarding tick-borne infections should be studied in these urban areas, where contacts between infected ticks and humans may be more frequent than elsewhere, due to high human activity. We examined the risk of encountering an infected tick in urban green spaces in Helsinki, Finland. We collected ticks at nine sites throughout Helsinki, recorded the prevalence of several pathogens and identified areas with a high potential for contacts between infected ticks and humans. Moreover, we explored the relationship between the density ofBorrelia burgdorferisensu lato-infected ticks and locally diagnosed cases of borreliosis and compared the potential for human-tick encounters in Helsinki to those in nonurban areas in south-western Finland. During 34.8 km of cloth dragging, 2,417Ixodes ricinuswere caught (402 adults, 1,399 nymphs and 616 larvae). From analysed nymphs, we found 11 distinct tick-borne pathogens, with 31.5% of nymphs carrying at least one pathogen. Tick activity was highest in August and September, leading to the density of nymphs infected withB. burgdorferis.l., and concurrently infection risk, to also be highest during this time. Nymph densities varied between the sampling sites, with obvious implications to spatial variation in infection risk. While ticks and tick-borne pathogens were found in both Helsinki and nonurban areas in south-western Finland, the estimates of human activity were generally higher in urban green spaces, leading to a higher potential for human-tick contacts therein. The presence of ticks and tick-borne pathogens and high local human activity in urban green spaces suggest that they form potential foci regarding the acquisition of tick-borne infections. Risk areas within cities should be identified and knowledge regarding urban ticks increased.